IMPLEMENTASI PERATURAN DESA KOMBA NOMOR 1 TAHUN 2017 TENTANG PENERTIBAN PEMELIHARAAN DAN KEPEMILIKAN TERNAK DI DESA KOMBA KECAMATAN KOTA KOMBA KABUPATEN MANGGARAI TIMUR - Dewalking, Marianus; Meyners, David; Tupen, Rafael R (Petitum Law Journal, 2024)
This study aims to evaluate the effectiveness of the implementation of Komba Village Regulation No. 1/2017 which regulates the control of livestock maintenance and ownership in Komba Village, Kota Komba Sub-district, East Manggarai Regency. The method used in this research is empirical juridical with data collection through observation and interviews. The results showed that the implementation of this regulation has not been fully effective. Many violations still occur in the field, such as livestock roaming in public places and damaging residents' crops. The main inhibiting factors include lack of socialization, low public awareness, and suboptimal supervision. The lack of socialization means that many residents do not understand the importance of this regulation, while old habits in livestock rearing are difficult to change. Limited supervision infrastructure also hampers the enforcement of the regulation. To improve effectiveness, a revision of the regulation with more appropriate sanctions, awareness raising, annual evaluation, and capacity building of village officials are required. The implementation of these suggestions is expected to improve community compliance and the effectiveness of regulation implementation, so that order and prosperity in Komba Village can be realized.